Tekstil atıksularının renksizleştirme işlemlerine genel bir bakış (2) - (:unkn) unknown (My University, 2004)
0

Since biological treatments are insufficient to decolouris textile waste waters, chemical treatments were developed such as oxidative, reductive, activated carbon, membrane, coagulation/flocculation, electrochemical, ion exchange treatmenst. Coloured textile waste wasters are extremely variable in composistion due to large numbers of dyes and this entails difficulty to choose the most suitable treatment for each textile miil. The choice of the type of treatment to be used for the decolourisation of textile waste waters depends on such properties as the molecular structure, molecular size, water solubility, dyeing properties, etc. of the dye and the chemicals used for dyeing. Assuming that the dyes and the dyeing chemicals can be virtually removed by membrane, oxidative technig ues or others the opportunity of reusing treated waste water, additionally dyes and chemicals in treated water may appear.
A general view of the decolorizing treatments of textile waste water (2)
Keywords: Malzeme Bilimleri, Tekstil